Take Advantage of AWWA's Operator Training and Education Resources. Issue 6 (8th July 2022) - Brewer, Todd; Weikel, Chad
Abstract : Water treatment and distribution operators are critical to delivering a reliable water supply as well as safeguarding the environment and protecting public health. AWWA is committed to providing the training resources needed to help operators address current and future challenges.